Correlation of serum myonectin concentrations with the presence and severity of obstructive sleep apnoea syndrome. (March 2021) - Zou, Huili; Yang, Weiyi; Liu, Yan
Objective: Myonectin, a newly discovered myokine, enhances fatty acid uptake in cultured adipocytes and hepatocytes and suppresses circulating concentrations of free fatty acids in mice. This study is performed to evaluate the association between serum myonectin concentrations with the presence and severity of OSAS. Methods: This study was performed in a population of 191 patients with OSAS and 105 control subjects. Serum myonectin concentrations were measured using enzyme-linked immunosorbent assay method. Results: Lower serum myonectin concentrations were found in OSAS patients than in the controls. Serum myonectin concentrations were associated with a reduced risk of OSAS (OR: 0.988, 95% CI: 0.984–0.993, P < 0.001). Severe OSAS patients had significantly lower myonectin concentrations compared with mild and moderate OSAS patients ( P < 0.001 and P = 0.001, respectively). There are lower serum myonectin concentrations in moderate patients compared with mild patients ( P = 0.024). Pearson correlation analysis revealed that serum myonectin concentrations were negatively correlated with the severity of OSAS (r = −0.344, P < 0.001). Simple linear regression analysis showed that serum myonectin concentrations in OSAS patients were negatively correlated with body mass index, fasting plasma glucose, homeostasis model assessment of insulin resistance (HOMA-IR), total cholesterol, low-density lipoprotein cholesterol (LDL-C) and apnoea hypopnea index. Multiple stepwise regression analysis shows that body mass index (β = −0.289, P = 0.03), HOMA-IR (β = −0.19, P = 0.003), total cholesterol (β = −0.155, P = 0.016), LDL-C (β = −0.176, P = 0.006) and apnoea hypopnea index (β = −0.263, P < 0.001) remained to be associated with serum myonectin. Conclusion: Serum myonectin concentrations are inversely correlated with the presence and severity of OSAS.